Summer of a thousand pies - Dilloway, Margaret (Balzer + Bray, an imprint of HarperCollins Publishers, 2019)
After her father goes to jail, Cady Bennett, twelve, is taken from foster care to spend a summer with her estranged Aunt Michelle, trying to save her failing pie shop.